Detection of tanB gene Streptococcus gallolyticus subspecies gallolyticus in stool of colorectal cancer patients - Ismail, Che Muhammad Khairul Hisyam; Hamzah, Hairul Aini; Mohammad Aidid, Edre; Shalihin, Mohd Shaiful Ehsan; Md Nor, Azmi (UPM, 2023)
Background: tanB gene encodes for tannase and is specific for Streptococcus gallolyticus subspecies gallolyticus (SGG). The human gut may be colonized by SGG through zoonotic transmission. Patients with colorectal carcinoma (CRC) have a higher SGG colonization rate than healthy humans. Therefore, the detection of tanB SGG in patients with early-stage CRC might be a useful screening tool. We aimed to establish a stool PCR technique without the need for bacterial cultures. Method: stool samples were collected from 113 patients, who were referred to SASMEC@IIUM health centre for colonoscopy. Bacterial DNA was directly extracted from the stool specimen before PCR. The PCR optimisation involved two pairs of primers targeting the tanB gene. DNA sequences of random samples were deduced by DNA sequencing and further analysed to determine the analytical specificity. The sensitivity of the technique was determined by a 10-fold dilution of a known standard. Results: Thirty-three (33) out of 113 patients were diagnosed with CRC. Upon optimization with two CRC samples, primer pair 1 showed a high analytical specificity of the PCR. The sensitivity of the assay reached 102 DNA copies/ml. As expected, further testing on all samples resulted in a higher rate of SGG detection in CRC samples (50%; n=16/33) compared to the non-CRC samples (20%; n=16/80). Conclusion: The established PCR technique potentially benefits early CRC diagnosis.